Q. 85.0( 1 Vote )

# Find what the given equation becomes when the origin is shifted to the point (1, 1).x2 – y2 – 2x + 2y = 0

Let the new origin be (h, k) = (1, 1)

Then, the transformation formula become:

x = X + 1 and y = Y + 1

Substituting the value of x and y in the given equation, we get

x2 – y2 – 2x + 2y = 0

Thus,

(X + 1)2 – (Y + 1)2 – 2(X + 1) + 2(Y + 1) = 0

(X2 + 1 + 2X) – (Y2 + 1 + 2Y) – 2X – 2 + 2Y + 2 = 0

X2 + 1 + 2X – Y2 – 1 – 2Y – 2X + 2Y = 0

X2 – Y2 = 0

Hence, the transformed equation is X2 – Y2 = 0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Various Forms of Equations of line45 mins  Parametric Equations of Straight line48 mins  Straight line | Analyse your learning through quiz56 mins  Slope, inclination and angle between two lines48 mins  Interactive Quiz on Equations of line23 mins  General Equation of a line43 mins  Motion in a Straight Line - 0665 mins  Motion in a Straight Line - 0556 mins  Motion in a Straight Line - 0372 mins  Motion in a Straight Line - 1063 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 